Comprehensive orthopedic dental rehabilitation for patients with excessive tooth abrasion and temporomandibular disorders - Макеєв, Валентин Федорович; Риберт, Юрій Олексійович; Магера, Наталя Сергіївна (Actual Dentistry, 2019)
Purpose. To increase the efficiency of dental rehabilitation of patients with excessive tooth abrasion and temporomandibular disorders (TMDs) through the development of the full range of measures for their orthopedic treatment. Methods. The general group included 68 patients, of these 31 (45.6 %) male and 37 (54.4 %) female aged 21 to 70. Patients were divided into two groups: the control group and the study group. The control group included 31 patients diagnosed with only excessive tooth abrasion in combination with possible other occlusal disorders. The study group included 37 patients with excessive tooth abrasion, possible other occlusal disorders and various forms of temporomandibular disorders: muscular, articular, and combined. Clinical methods were applied for determining the state of the dentoalveolar complex in patients with excessive tooth abrasion and TMDs including: radiological – to study and visualize structural parts of the dentoalveolar complex; axiographic – to determine the functional state of the temporomandibular joints and to analyze functional occlusion in an articulator configured for individual function; statistical – to assess the probability of the results obtained. Results. Dental rehabilitation of patients with excessive abrasion of hard tissues of teeth was conducted taking into account the involvement of the temporomandibular joint in the pathological process and was aimed at complete or partial restoration of functional disorders in masticatory muscles and temporomandibular joints and compensation of missing functions of the affected organs or systems (restoration of teeth, dentition). Conclusions. The effectiveness of treating patients with excessive tooth abrasion and TMDs is achieved through the individualization of therapeutic and rehabilitation measures, which should include the use of medical diagnostic devices (occlusal splints, orthotic devices, temporary orthodontic appliances). The purpose of these measures is to achieve the optimal position of the mandibular condyles followed by a mandatory restoration or reconstruction of functional occlusion, which is a prerequisite for complete morphofunctional rehabilitation. In the absence of an individual approach, there is a high risk of development of various kinds of iatrogenesis, as well as the timing of adaptation increases or adaptation to dentures is incomplete, which is a sign of incomplete morphofunctional rehabilitation. Key words: excessive tooth abrasion, temporomandibular disorders, orthopedic treatment.